(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Alginate-gelatin hydrogels are commonly utilized as bioink components in bioprinting. To improve the structural integrity of bioprinted objects made from these hydrogels, ionic crosslinking is typically conducted using calcium chloride, usually after the entire object has been printed. This study investigates the effects of inter-layer crosslinking applied between the deposition of successive printing layers on layer adhesion. The primary research questions are: Does inter-layer crosslinking enhance or diminish layer adhesion? Can these effects be modulated by adjusting inter-layer crosslinking parameters, such as the duration of crosslinking before the deposition of the next layer? To address these questions, test structures are printed using a commercial bioprinter (CELLINK BIO X6, CELLINK, Gothenburg, Sweden). The test structures consist of two-layer rectangular shapes measuring 30 mm by 30 mm. After extruding the first layer of hydrogel, calcium chloride is applied as a crosslinker using drop-on-demand printing. Subsequently, the second layer of hydrogel is extruded using a pneumatic printhead. The central parameters varied include calcium chloride concentration, extrusion volume of calcium chloride, and the time interval between crosslinker application and the extrusion of the second layer. Preliminary findings indicate that inter-layer crosslinking can enhance the overall structural integrity of the object, while reduced layer adhesion may facilitate object separation, such as detaching the target object from support structures.